A Role of Literacy in Raising Awareness of Waqf for Sustainable Development - Dariyanto, Erwin (The Indonesian Forestry Certification Cooperation, 2024)
Indonesia has a very large waqf potential, namely 57,763 hectares of land spread across 440,512 locations. Likewise, the potential for cash waqf reaches IDR 180 trillion per year. Another fact is that the majority of Indonesia's population, namely 87.08 percent or around 245,973,915 people, are Muslim. However, the large number of Muslims in Indonesia is not directly proportional to the absorption of waqf potential. From 2010 to 2020, only IDR 391 billion in cash waqf funds were collected. It was only in 2021 to 2023 that there was a spike in the absorption of cash waqf to IDR 2.3 trillion in 2023. This study aims to examine the role of literacy in increasing awareness of waqf for sustainable development. The study was conducted using a qualitative descriptive analysis method. The data sources used in this study are statements from figures or officials, documents, data on the absorption of cash waqf, and laws and regulations on waqf in Indonesia. The results show that literacy is very important and has a great influence on the absorption of cash waqf potential in Indonesia. The community will be motivated to make waqf when they have sufficient knowledge about waqf. It is hoped that this study can be an input for policy makers to further improve literacy strategies so that the large potential of waqf in Indonesia can be maximally absorbed.